2021
DOI: 10.1002/mrm.29131
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and robustness of MP‐GRASP T1 mapping

Abstract: To demonstrate the repeatability of fast 3D T 1 mapping using Magnetization-Prepared Golden-angle RAdial Sparse Parallel (MP-GRASP) MRI and its robustness to variation of imaging parameters including flip angle and spatial resolution in phantoms and the brain. Theory and Methods:Multiple imaging experiments were performed to (1) assess the robustness of MP-GRASP T 1 mapping to B 1 inhomogeneity using a single tube phantom filled with uniform MnCl 2 liquid; (2) compare the repeatability of T 1 mapping between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Earlier studies have reported that this can be achieved with a model-based reconstruction. 24,25 It has also been shown that model-based reconstructions can become unstable for non-linear models 26 similar to the one presented in Equation (8) and should be linearized. To linearize a non-linear signal model such as the one shown in Equation ( 8), principal component analysis (PCA) can be used.…”
Section: Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have reported that this can be achieved with a model-based reconstruction. 24,25 It has also been shown that model-based reconstructions can become unstable for non-linear models 26 similar to the one presented in Equation (8) and should be linearized. To linearize a non-linear signal model such as the one shown in Equation ( 8), principal component analysis (PCA) can be used.…”
Section: Techniquementioning
confidence: 99%
“…3 Further, due to the VFA method's known sensitivity towards excitation RF field (B 1 ) inhomogeneity, a separate B 1 measurement is usually required. 7 The Look-Locker method, on the other hand, is known to be insensitive to B 1 inhomogeneity, 8 but its original version requires a long acquisition time. 9 There is on-going research to enable clinically practical imaging time for the Look-Locker method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the flexibility to provide varying temporal resolution with golden‐angle radial sampling can be exploited to reconstruct the same DCE‐MRI dataset for simultaneous qualitative assessment (with low temporal resolution) and quantitative perfusion analysis (with high temporal resolution). In addition, stack‐of‐stars golden‐angle radial sampling has also been demonstrated for imaging nonmoving organs in neuroimaging, 51,92 and it is also good for quantitative MRI, such as MR parameter mapping 48,51,93,94 …”
Section: Golden‐angle Radial Sampling: Recommendations and Applicationsmentioning
confidence: 99%
“…In addition, stack-of-stars golden-angle radial sampling has also been demonstrated for imaging nonmoving organs in neuroimaging, 51,92 and it is also good for quantitative MRI, such as MR parameter mapping. 48,51,93,94 Stack-of-stars golden-angle radial sampling is often compared against 3D golden-angle Cartesian sampling, in which the phase-encoding steps in the ky-kz plane can be segmented into different interleaves rotated by the golden angle. [95][96][97] The main advantage of the 3D golden-angle Cartesian trajectory is that all k-space data are sampled directly on a Cartesian grid, so that the time-consuming NUFFT is not needed for image reconstruction.…”
Section: Stack-of-stars Golden-angle Radial Samplingmentioning
confidence: 99%